1975
DOI: 10.1073/pnas.72.7.2719
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of delta-aminolevulinic acid from the intact carbon skeleton of glutamic acid in greening barley.

Abstract: The customary route in animals and bacteria for 6-aminolevulinic acid biosynthesis is from glycine and succinyl CoA, tamine were more effective in labeling the ALA (9, 10). Therefore, an alternative route of synthesis of ALA in plants appeared to be indicated. In this paper we report the labeling of specific carbon atoms of ALA by specifically labeled glutamate, clearly indicating that the five-carbon skeleton of glutamate is incorporated intact into ALA. We discuss possible biochemical routes of the labelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
1
6

Year Published

1977
1977
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(87 citation statements)
references
References 28 publications
1
79
1
6
Order By: Relevance
“…This difference is also evident when the two precursors are examined for their ability to label ALA in vivo (3,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference is also evident when the two precursors are examined for their ability to label ALA in vivo (3,24).…”
Section: Discussionmentioning
confidence: 99%
“…as a precursor of ALA both in detached leaves and in isolated etio-chloroplasts (3,10,24); the occurrence of alanine:DOVA transaminase in several algae (9,21,31); the cofactor requirement for the conversion of labeled KG to [14CIALA in cell-free systems (16,31); the isolation of DOVA from greening cultures of the C-2A' mutant of Scenedesmus obliquus (4,30) and, finally, the demonstration that a considerable part of the ALA formed in greening leaves of both maize and barley was obtained by removal and reinstatement of the amino group of glutamate (15). This last observation is not consistent with the suggested route through glutamate-l-semialdehyde (15).…”
mentioning
confidence: 99%
“…A prerequisite for further studies of the genetic regulation of chlorophyll biosynthesis (9,13,21) is the isolation and characterization of the enzyme(s) converting glutamate into baminolevulinate (ALA) (3,4). Recently it has been shown that ALA formation can be carried out by isolated intact immature chloroplasts of spinach (7) and cucumber (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of b-aminolevulinate (ALA) in higher plants has been actively investigated in recent years (1,2,4,6,8,9,10,11) but there is little information on the enzyme or enzymes involved, because of the difficulties encountered in obtaining active organelle-free preparations. LOHR and FRIEDMANN partially purified two enzymes from maize leaf extracts, one catalyzing the conversion ofa-ketoglutarate into dioxovalerate in the presence of NADH and the other involved in the transamination of dioxovalerate into ALA (8).…”
Section: Introductionmentioning
confidence: 99%